Thinking Styles among Technical Students in TVET: Differences in Thinking Styles by Students' Demographic - Hamdan, Nuraffefa; Mei Heong, Yee; Ibrahim, Badaruddin; Mohamad, Mimi Mohaffyza (Journal of Technical Education and Training, 2021)
A thinking style is the way an individual acquires, processes and organises information, as well as forming ideas and views, solving problems, making decisions and articulating self-expression. Each individual has his or her own style of thinking in learning, solving problems, or even in designing products. The purpose of this study is to analyse the pattern of Chua thinking styles among technical students. A total of 351 technical students comprising of Civil Engineering, Mechanical Engineering and Electrical Engineering students at Sultan Abdul Halim Muad'zam Shah Polytechnic were randomly selected as the study sample. The design of this study was a form of survey study using a quantitative approach. The Yan Piaw Creative-Critical Styles Test, developed by Chua (2004), was used as the research instrument. Data were analysed using SPSS software and presented in the form of mean, frequency, and percentage. The findings show that the dominant thinking style is the balanced thinking style, with 166 respondents (47.3%). It is followed by the critical thinking style in 153 respondents (43.6%) and the creative thinking style in 32 respondents (9.1%). However, none of the students has a high creative thinking style and a high critical thinking style. The findings also show that there is no statistically significant difference in Chua thinking styles by gender, age, years of study and field of study. In general, it can be concluded that technical students are most inclined to a balanced thinking style, which is to have a balanced thinking in terms of creative and critical thinking styles. As such, an individual's thinking style will have an impact on learning to solve problems in product design.